(untitled) (Research, Society and Development, 2022)
The aim of the present study was to review the physical therapy interventions performed individually or in combination in individuals with knee osteoarthritis. The search for the theoretical framework was carried out in the Scielo database, as well as in Google Scholar, where once the articles were found, in addition to the analysis, they will be interpreted and classified as the most used and/or most effective physiotherapeutic approaches in the treatment of Osteoarthritis of knee. Twenty-one articles were included in the research, presenting kinesiotherapy/physical activity as the most used therapeutic approach, followed by Electrotherapy, Aquatic Physiotherapy, Phototherapy, in addition to combined therapies and less traditional therapies such as: Craniopuncture, Geotherapy, Phytotherapy and elastic knee pads. The research concluded that the methods evaluated showed improvement in at least one symptom of Osteoarthritis, with kinesiotherapy standing out positively, since the strengthening of the muscles of the lower limbs contributed positively to most symptoms of Knee Osteoarthritis.